The effects of strength and conditioning interventions on sprinting performance in team sport athletes: a systematic review and meta-analysis - Murphy, A.; Burgess, K.; Hall, A. J.; Aspe, R. R.; Swinton, P. A. (The Journal of Strength and Conditioning Research, 2023)
Linear sprinting is a key determinant of athletic performance within team sports. The aims of the review were to quantify and compare the effectiveness of popular strength and conditioning (S&C) training modes to improve sprint performance in team sport athletes, with additional focus on potential moderators and the relationships between improvements in physical factors (e.g., strength, power, and jump performance) and improvements in sprint performance. Inclusion was restricted to resistance, plyometric, sprint, and combined training interventions comprising team sport athletes. Multilevel, Bayesian`s meta-analysis and meta-regression models conducted with standardized mean difference effect sizes were used to investigate training modes and potential moderators. Weighted regression models conducted on shrunken estimates from initial Bayesian`s meta-analyses were used to quantify relationships between improvements in physical factors and sprint performance. Certainty of evidence was assessed using the grading of recommendations assessment development and evaluation (GRADE) approach. Similar improvements in sprint performance were obtained across training modes, with some evidence of the largest effects with resistance training (SMD_pre0.5) = 0.55 [95% credible interval [CrI]: 0.36-0.78; very low certainty]). A strong moderating effect of training intensity was identified across all training modes with evidence of greater improvements in sprint performance with high-intensity training (beta_low:high0.5 = 0.17 [95% CrI: 0.01-0.33; very low certainty]). Strong positive relationships were identified between improvements in all physical factors and sprint performance (beta_strength0.5 = 0.56 [95% CrI: 0.36-0.77; low certainty], beta_power0.5 = 0.80 [95% CrI: 0.50-1.0; low certainty], beta_jump0.5 = 0.78 [95% CrI: 0.57-0.97; low certainty]). The findings indicate that focus on developing speed in team sport athletes should be placed on S&C training with high intensities, including the use of resisted sprint training